The Effects of Yoga on Patients with Parkinson’s Disease: A Meta-Analysis of Randomized Controlled Trials - Mengke Ban; Xuejing Yue; Pengyu Dou; Ping Zhang (Behavioural Neurology)
Background and Purpose. The manifestations of motor and nonmotor dysfunctions in Parkinson’s disease (PD), which are intimately connected, have been shown to reduce quality of life (QoL). It has been demonstrated that yoga could benefit PD patients. However, there was no consensus on the impact of yoga on PD. This meta-analysis is aimed at investigating the effects of yoga intervention on motor function, nonmotor function, and QoL in patients with PD. Methods. A meta-analysis was conducted by systematically searching PubMed, Embase, and Cochrane Library databases till August 2020 for studies published in English. The reference lists of eligible studies were also searched. The motor symptoms (UPDRS-Part III), balance function (BBS and BESTest), functional mobility (TUG), anxiety (HADS and BAI), depression (HADS and BDI), and the quality of life (PDQ-39 and PDQ-8) were the primary evaluation indexes. Results. Ten studies including 359 participants were included in this meta-analysis. The pooled results showed significant difference between the yoga training group and the control group. Patients in the yoga training group had better functional outcomes in terms of motor status (MD=−5.64; 95% CI, -8.57 to -2.7), balance function (SMD=0.42; 95% CI, 0.08 to 0.77), functional mobility (MD=−1.71; 95% CI, -2.58 to -0.84), anxiety scale scores (SMD=−0.72; 95% CI, -1.01 to -0.43), depression scale scores (SMD=−0.92; 95% CI, -1.22 to -0.62), and QoL (SMD=−0.54; 95% CI, -0.97 to -0.11). Conclusion. Our pooled results showed the benefits of yoga in improving motor function, balance, functional mobility, reducing anxiety and depression, and increasing QoL in PD patients.